2012
DOI: 10.1161/circulationaha.112.092643
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Wait-List Outcomes in Patients Listed for Heart Transplantation in the United States

Abstract: Background-Racial differences in long-term survival after heart transplant (HT) are well known. We sought to assess racial/ethnic differences in wait-list outcomes among patients listed for HT in the United States in the current era. Methods and Results-We compared wait-list and posttransplant in-hospital mortality among white, black, and Hispanic patients Ն18 years of age listed for their primary HT in the United States between July 2006 and September 2010. Of 10 377 patients analyzed, 71% were white, 21% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…(39) This could be beneficial to racial/ethnic minorities who were more likely to be listed if an inotrope was indicated in their care. (40) However guidelines for transplantation are not concrete. Conservative transplantation programs may place greater weight on insurance type when deciding which candidates should be listed for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…(39) This could be beneficial to racial/ethnic minorities who were more likely to be listed if an inotrope was indicated in their care. (40) However guidelines for transplantation are not concrete. Conservative transplantation programs may place greater weight on insurance type when deciding which candidates should be listed for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite constituting an increasing percentage of heart transplant candidates, racial minorities continue to be listed for transplant at a later stage in their disease process and are at higher risk for adverse outcomes in both the pre-and posttransplant phases. 42 Relative to whites, black transplant recipients have been shown to have less generous health insurance policies and lower adherence to immunosuppression, both of which are felt to contribute to poorer outcomes in this population. 43,44 Articles in this section examine multiple topics in HF including racial differences in the efficacy of β blocker therapy, trends by race in the use of implantable cardioverter defibrillators, the impact of acculturation on HF outcomes, and differences by race in the care and outcomes of heart transplantation patients.…”
Section: Heart Failurementioning
confidence: 99%
“…8 African Americans were much sicker at the time of transplant, with 74.3% patients in UNOS status I. Singh et al also reported similar findings in their study, in which AA and Hispanic patients were more likely to be listed with higher urgency (UNOS status I) compared with white patients (P < 0.001). 19 Despite this difference, we noted that survival among AA patients was significantly worse compared with non-AA patients within individual UNOS class.…”
Section: Discussionmentioning
confidence: 77%